A Survey on Technical Aspects of MAC 802.11b and MAC 802.16e - Gaur, Shaili; Singh, Rajnesh (International Journal of Computer Sciences and Engineering, 2015)
With the increasing use of small and handheld devices, wireless and mobile networks have experienced an unprecedented growth. But their performance significantly depends on the choice of suitable MAC protocol which aims at coordinating access to the shared wireless medium among a number of mobile nodes. Several wireless standards have developed for supporting wireless and mobile networking. Various versions of IEEE 802.11 (Wi-Fi) and IEEE 802.16 (mobile WiMAX) offer physical and MAC layer specifications for WLAN and WMAN respectively. This paper presents a detailed description of the design and technical aspects of MAC 802.11b and MAC 802.16e.